Die deutsche Fischerei auf Köhler im Nordost-Atlantik 1979 - Reinsch, H.H. (1980)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010